Fibromyalgia with psoriatic and rheumatoid arthritis: relationship with disease activity and serum vitamin D level - Hanan S. Abozaid; Alshimaa Hamdy Khalaf; Dalia S. Elgendy; Rabab Hussein Ali Ahmed (Egyptian Rheumatology and Rehabilitation, 2023)
Abstract Background The study of the relationship between the presence of fibromyalgia (FM) with rheumatoid (RA) and psoriatic arthritis (PsA) patients can affect the main disease outcome and the treatment decision. The research aims to assess the associated fibromyalgia and vitamin D level in rheumatoid and psoriatic arthritis patients. Results A cross-sectional study included 60 RA, 30 PsA, and 40 healthy controls, all of them were evaluated for the diagnosis of FM and serum vitamin D level, disease activity score 28 (DAS28), and health quality of life. The mean age of RA was 47.75 ± 11.11 SD, for PsA 44.17 ± 10.8 SD, and for the controls 44.35 ± 13.64 with no significant differences. FM was diagnosed in 21.7% of RA, 13.3% of PsA, and 2.5% of healthy controls with a significant difference among the three groups (P value = 0.025). RA and PsA patients with concomitant FM showed statistically significant higher disease activity scores, significantly worse quality of life than those without FM, and significantly lower serum vitamin D than those without FM. Conclusion Vitamin D deficiency and the presence of FM can be related to higher disease activity and less response to treatment, early recognition and treatment of FM and vitamin D deficiency in RA and PsA patients could be important to obtain a good response to therapy and achieve remission.